Measuring Location Dominance Based on Public Service Accessibility: Case Study of Shijiazhuang, China - Yuan Wang; Peipei Pan; Lijie Pu (Land)
The spatial equality of urban public services and their accessibility are a crucial aspect of urban sustainability. However, there is currently a lack of a composite proxy that can effectively assess public service equality with fine granularity. To address this gap, we have developed a new indicator based on the concept of location dominance. This indicator accumulates access opportunities to public services with a time-weighted decay function at granular level. Our findings reveal that location dominance in Shijiazhuang follows a pronounced core–periphery pattern. Efficient travel modes can significantly enhance location dominance and increase spatial equality, aligning with people’s travel preferences. Additionally, we discovered an extremely strong linear correlation between three key urban development elements (i.e., nighttime lighting data, land use intensity, and population retention rate) and location dominance. The discussion of these findings confirms the validity of our method and the reliability of our results. Consequently, this method and its outputs can aid policymakers and urban planners in swiftly identifying subtle disparities in spatial accessibility for public services, thereby promoting urban equality and sustainability.